Next-generation nutrition: Innovative and AI-tailored concentrated ingredients - Jerina Rugji; Zeki Erol; Ambreen Hamadani; Migena Gjoni Gündemir; Fulya Taşçı; Laura Musa (Trends in Food Science & Technology, 2026)

In vitro antibacterial activity of hemp (Cannabis sativa L.) extract seed oil against multidrug resistant bacterial pathogens in small animal veterinary dermatology - Valeria Toppi; Mattia Pirolo; Elisa Rampacci; Gabriele Scattini; Laura Musa; Giorgia della Rocca; Alessandra Di Salvo; Marina De Benedetti; Luca Guardabassi; Patrizia Casagrande Proietti (The Veterinary Journal, 2025)

Utilization of AI – reshaping the future of food safety, agriculture and food security – a critical review - Jerina Rugji; Zeki Erol; Fulya Taşçı; Laura Musa; Ambreen Hamadani; Migena Gjoni Gündemir; Esa Karalliu; Shahida Anusha Siddiqui (Critical Reviews in Food Science and Nutrition, 2025)

Fecal carriage of extended-spectrum beta-lactamase (ESBL)-producing Escherichia coli in South American camelids and biosecurity practices among farms in northern Italy - Laura Filippone Pavesi; Maria Cristina Rapi; Martina Penati; Laura Musa; Federica Santandrea; Vincenzo Ferrulli; Ilaria Martucci; Antonio Boccardo; Guido Grilli; Maria Filippa Addis; Valerio Bronzo (Veterinary Research Communications, 2025)
South American camelids (SACs), particularly llamas ( Lama glama ) and alpacas ( Vicugna pacos ) are gaining popularity in Europe. Initially valued for their fiber and land management capabilities, these animals are now also kept for animal therapy, outdoor activities, and as companion animals. Despite their close interactions with humans and other animals, there is limited research on the transmission of microbes or antimicrobial resistance genes from SACs. This study aimed to survey the fecal carriage of extended-spectrum beta-lactamase ESBL-producing Escherichia coli (ESBL - E. coli) in SACs. A questionnaire was administered on-site to the farmers to survey management and biosecurity measures. Twelve farms from northern Italy (Lombardy, Piedmont, Veneto, and Emilia-Romagna) participated in the study. Fecal samples were analyzed to identify ESBL- E. coli and subjected to bacteriological culture on CHROMagar™ ESBL plates. Isolate identification was accomplished by MALDI-TOF MS, then subjected to the double-disk synergy test (DDST) and examined for 3 ESBL-encoding genes ( bla CTX−M , bla TEM , bla SHV ) via PCR analysis. A total of 125 SACs (19 llamas and 106 alpacas) were included. Four (3.2%) of these animals were positive for ESBL- E. coli . Two isolates carried the bla CTX−M gene; one had both bla CTX−M and bla TEM , and one was negative for all ESBL-encoding genes. Furthermore, none of the ESBL- E. coli isolates tested positive for the bla SHV gene. Several data from our questionnaire revealed a lack of biosecurity protocols, which aligns with other studies. The prevalence of ESBL-producing bacteria identified in this study was lower than in different other studies. Despite the low biosecurity levels observed on the SAC farms, our findings showed a low occurrence of ESBL- E. coli and a low carriage rate of multidrug-resistant (MDR) ESBL- E. coli .

High prevalence and genetic heterogeneity of adenoviruses at a psittacine breeding facility - Gabriele Lizzi; Simone Fasana; Guido Grilli; Giulia Quaglia; Sara Pedrazzoli; Giulia Graziosi; Elena Catelli; Laura Musa; Maria Cristina Rapi; Caterina Lupini (Veterinary Research Communications, 2024)
A polymerase chain reaction (PCR) survey was performed at an amateur parrot breeding facility in Italy to investigate the presence and molecular characteristics of adenoviruses. Eighty psittacine birds, belonging to seven parrot species, were sampled by cloacal swabs; in addition, 15 livers were collected from specimens that were found dead. Seventy-two out of 95 samples collected were positive for adenoviruses, with a prevalence rate of 75.8%. All seven psittacine species tested positive for at least one genus of the family Adenoviridae ; notably, adenoviral infection was found for the first time in the hooded parrot ( Psephotellus dissimilis ). Based on the sequences and phylogenetic analysis, 57 sequences were psittacine adenovirus 2, seven sequences were duck adenovirus 1 and two sequences were identified as psittacine adenovirus 5. The six remaining sequences showed low nucleotide and amino acid identity with the reference strains of accepted species or types, revealing the presence of novel adenoviruses belonging to the genera Aviadenovirus , Barthadenovirus and Siadenovirus . There were identical adenovirus sequences in both apparently healthy and dead birds suggesting that further investigation into the role and impact of these viruses on the health of psittacine birds is warranted.

Linking household access to food and social capital typologies in Phalombe District, Malawi - Ailish Craig; Craig Hutton; Laura A. Lewis; Frank B. Musa; Justin Sheffield (Sustainability Science, 2023)
Food security remains a major sustainability challenge in many parts of Sub-Saharan Africa. Food security has numerous determinants that are complex and interlinked, with one of them being social capital. Social capital reflects an individual’s, household’s, or community’s social networks, social interactions, and social support systems that can be mobilized in times of need to maintain, among others, livelihoods or food security. This study aims to further understand how typologies of social capital are associated with household food security in Southern Malawi, with a focus on access to food. We unpack social capital into three typologies, namely bonding, bridging, and linking social capital, and establish which one is most strongly associated with household access to food, and whether this varies by the gender of the household head. To achieve this, we analyze secondary data from 382 households collected through the Malawian Fourth Integrated Household Survey (IHS4), using principal axis factor analysis and logistic regression analysis. Our findings demonstrate that bonding and bridging social capital are associated with better household access to food, while linking social capital was associated with lower household access to food. Bonding social capital was most strongly associated for female-headed households and linking social capital for male-headed households, highlighting that there are differences between such households. This work confirms observations from other related studies in Sub-Saharan Africa exploring the interface of social capital and food security. It also highlights the importance of both acknowledging the gender of the household head and of unpacking social capital into its typologies when considering food security.

Healthcare Economics of Hydrocephalus After Aneurysmal Subarachnoid Hemorrhage in the United States - Syed M. Adil; Beiyu Liu; Lefko T. Charalambous; Musa Kiyani; Robert Gramer; Christa B. Swisher; Laura Zitella Verbick; Aaron McCabe; Beth A. Parente; Promila Pagadala; Shivanand P. Lad (Translational Stroke Research, 2019)

Improving household food security in eastern Democratic Republic of the Congo: a comparative analysis of four interventions - Shannon Doocy; Jillian Emerson; Elizabeth Colantouni; Johnathan Strong; Kimberly Amundson Mansen; Laura E. Caulfield; Rolf Klemm; Laura Brye; Sonya Funna; Jean-Pierre Nzanzu; Espoir Musa; Jozimo Santos Rocha; et al. (Food Security, 2018)

Curie Point Depth Estimates from Aeromagnetic Data from Death Valley and Surrounding Regions, California - Musa Hussein; Kevin Mickus; Laura F. Serpa (Pure and Applied Geophysics, 2013)